PENGARUH LATIHAN TENDANGAN MENGGUNAKAN KAKI DALAM DAN PUNGGUNG KAKI PENUH TERHADAP KETEPATAN SHOOTING KE GAWANG. - Rian Arya Putra; Mikhael Jeremia Pangihutan Simanjuntak; Gilang Seprima Saqi; Afrianto Gunawan; Virhot Junanda Silalahi; Ely Yuliawan; Mohd. Adrizal (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The accuracy of shooting on goal is a critical factor in a football team's success in scoring goals; however, low shooting accuracy among young players remains a common problem observed in the field. This study aimed to determine the effect of kicking practice using the inside-of-the-foot technique and the full-instep technique on shooting accuracy on goal, as well as to compare the effectiveness of the two training methods. The study employed an experimental method with a pre-test and post-test group design. The research sample consisted of 20 male players selected through purposive sampling and divided into two groups using the matched-pair technique with the ABBA formula, namely experimental group I (inside-of-the-foot training) and experimental group II (full-instep training), each comprising 10 players. The treatment was administered over 14 sessions, and shooting accuracy was measured using a target-shooting test at a distance of 16.5 meters. Data were analyzed using normality tests, homogeneity tests, and t-tests with the assistance of SPSS 16. The results showed that the mean score of the inside-of-the-foot group increased from 13.40 to 21.70, while the mean score of the full-instep group increased from 13.80 to 24.30. The paired-sample t-test indicated a significant effect in both groups (p = 0.000), while the independent-sample t-test indicated a significant difference between the two groups (p = 0.032). It is concluded that training using the full instep of the foot is more effective than training using the inside of the foot in improving shooting accuracy on goal